1992
DOI: 10.1002/jmv.1890380303
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnosis of chronic hepatitis C virus infection by detection of antibody to multiple epitopes: Confirmation by antibody to synthetic oligopeptides

Abstract: Serum samples from 226 patients covering a wide spectrum of liver disease were tested for antibodies to hepatitis C virus (HCV) using both first and second generation enzyme linked immunosorbent assays. Selected sera were also tested by peptide immunoassays, by the four-antigen recombinant immunoblot assay (RIBA II), and for viral genome by the polymerase chain reaction. Antibody to c100-3 was detected in 61% of patients with chronic non-A, non-B (NANB) hepatitis and/or 46.5% with presumed NANB-related cirrhos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The presence of HCV RNA in serum was determined by reverse-transcription nested polymerase chain reaction (RT-PCR) using primers from the 5Ј NCR region, as described previously [Brown et al, 1992] .…”
Section: Hcv Rna Detectionmentioning
confidence: 99%
“…The presence of HCV RNA in serum was determined by reverse-transcription nested polymerase chain reaction (RT-PCR) using primers from the 5Ј NCR region, as described previously [Brown et al, 1992] .…”
Section: Hcv Rna Detectionmentioning
confidence: 99%
“…Evidence of HCV infection is found in 60 to 100% of patients with chronic hepatitis when other causes are excluded and EIA-2 screening tests are used (38,118,148,260,311). Higher rates of HCV infection are observed in Japan and Mediterranean countries, and lower rates are seen in the United States and the United Kingdom.…”
Section: Chronic Hepatitismentioning
confidence: 99%
“…Details of the PCR method were as described by Brown et al [1992]. In short, 5 pl of the cDNA solution was added to a first round PCR mix containing 50 pM of each of the outer primers, 0.2 mM dNTPs, 10 p1 of l o x Taq polymerase buffer, 1.5 mM MgCl,, and 2.5 U of Taq DNA polymerase (Gibco) in a total reaction volume of 100 pl overlaid with a few drops of mineral oil (Sigma).…”
Section: Pcrmentioning
confidence: 99%
“…Hepatitis C virus (HCV) was first identified [Choo et al, 19891 and shown to be a small enveloped RNA virus 0 1994 WILEY-LISS, INC. [Houghton et al, 19911 using molecular biological techniques. The polymerase chain reaction (PCR) has been used by many investigators to detect HCV-RNA in serum [Garson et al, 1990;Brown et al, 1992;Kato et al, 1993;Yun et al, 19931 or liver tissue LWeiner et al, 1990;Shieh et al, 1991;Sallie et al, 19921 of patients with hepatitis C. In contrast with the delayed appearance of anti-HCV (30-90 days postinfection), detection of serum HCV-RNA by PCR is a n early event, occurring as soon as 5-10 days after infection [Trepo et al, 19931. A major advantage of the PCR technique is its extreme sensitivity that has led to the detection of a low copy number of virus in individuals who were negative for conventional viral markers [Bonino et al, 19921. While allowing a direct and highly sensitive identification of viral genome, PCR however, has certain limitations imposed, for example, by possible contamination problems [Brechot, 19931. Recently, 31 laboratories cooperated in a quality control study for detecting HCV-RNA in serum by PCR; false-negative as well as falsepositive results were reported [Zaaijer et al, 19931. Bresters et al [1992] reported a 100% correlation between HCV cDNA-PCR results from plasma, freshfrozen and formalin-fixed, paraffin embedded (FFPE) liver tissue of patients with chronic non-A, non-B hepatitis who had not been treated with antiviral agents.…”
Section: Introductionmentioning
confidence: 99%